PENERAPAN MANAJEMEN STRATEGI UMKM DALAM MENGHADAPI PERSAINGAN BISNIS DI KAWASAN PPS Al-UTSMANI BONDOWOSO - Haqiqotus Sa’adah; Kazimah; Sri Yuliati Ningsih; Ainur Rohmah; Muhammad Bahanan (IZZI: Jurnal Ekonomi Islam, 2024)
Micro, Small and Medium Enterprises or UMKM are the business group that has the largest number and has proven to be resistant to various shocks from the economic crisis. Strategy is very important to determine the company's success in achieving its long-term goals. By choosing the right strategy for a particular company position, a company will have a competitive advantage. The aim of this research is to find out what strategies are used by Micro, Small and Medium Enterprises (UMKM) owners in facing business competition. This research method uses descriptive qualitative, previously interviews were conducted with resource persons with the results obtained in the form of strategies implemented by sellers in promoting the goods they sell. It can be concluded that business competition in the Al-Utsmani Salafiyah Islamic boarding school is so great that sometimes business actors are at a disadvantage in dealing with this situation, therefore business strategies play a very important role.